Pull-through technique of scapular osteocutaneous flap to decrease frequency of positioning change - K. Hasegawa,* H. Miyamoto,* K. Fujita (Blackwell Synergy, 2000)
Removal of a tumour and raising a flap are usually done simultaneously by two teams. In cases of the scapular flap, however, they cannot be done simultaneously. Two changes of position are required to remove the tumour, harvest the flap and reconstruct the head and neck.